The central Fuegian fold and thrust belt in Tierra del Fuego: Strike‐slip tectonics superimposed onto compressional deformation. (20th February 2020) - Lozano, Jorge G.; Bran, Donaldo M.; Peroni, Javier I.; Lodolo, Emanuele; Menichetti, Marco; Cerredo, María E.; Tassone, Alejandro
Abstract : The boundary between South America and Scotia plates was established during Neogene times when a wrench tectonic regime was developed along the central area of Tierra del Fuego. This boundary includes the Magallanes–Fagnano fault system: a regional diffuse deformation zone, which involves the development of the satellite Yehuin–Chepelmut fault zone and a series of pull‐apart basins overprinting the Fuegian fold and thrust belt. The analysis of regional seismic lines allowed to reconstruct and recognize the structure of the external fold and thrust belt. The interpreted structures were integrated into a regional transect and a 3D block diagram that display the different structural domains and, mainly, the wrench deformation associated with the Magallanes–Fagnano fault system. Geophysical data from gravity and magnetic anomaly maps provided further support for the location and development of the pull‐apart basins along the plate boundary. The deformation of the external fold and thrust belt is characterized by an imbricated fan system with a Paleogene detachment surface, which was later cut across by the Yehuin–Chepelmut fault zone and the Magallanes–Fagnano fault system.